Роль територіальних громад у забезпеченні розвитку інноваційно-інтегрованих структур в умовах децентралізації - Зайченко, В. В.; Zaichenko, V. (ЦНТУ, 2018)
Стаття присвячена дослідженню ролі територіальних громад у забезпеченні сталого розвитку інноваційно-інтегрованих структур різного типу під час активізації процесу децентралізації влади й управління в Україні. Охарактеризовано сутність інтеграційних кластерних утворень та доведена доцільність використання сучасних технологій стратегічного менеджменту задля ефективного управління створенням і функціонуванням інноваційно-інтегрованих структур у межах територій. Наведено ключові критерії оцінки результатів впровадження децентралізації. Здійснено аналіз регіональних відмінностей щодо кількості Об’єднаних територіальних громад та рівня охоплення ними населення, оцінено індикатори моніторингу фінансової підтримки процесу децентралізації влади за регіонами України. Визначено позитивний ефект від розвитку інноваційно-інтегрованих структур для основних стейкхолдерів (держави, територіальних громад, бізнес-структур, інвесторів, освітніх і наукових установ). Статья посвящена исследованию роли территориальных общин в обеспечении устойчивого развития инновационно-интегрированных структур различного типа при активизации процесса децентрализации власти и управления в Украине. Охарактеризованы сущность интеграционных кластерных образований и доказана целесообразность использования современных технологий стратегического менеджмента для эффективного управления созданием и функционированием инновационно-интегрированных структур в пределах территорий. Приведены ключевые критерии оценки результатов внедрения децентрализации. Осуществлен анализ региональных различий по количеству Объединенных территориальных общин и уровню охвата ими населения, оценены индикаторы мониторинга финансовой поддержки процесса децентрализации власти по регионам Украины. Определен положительный эффект от развития инновационно-интегрированных структур для основных стейкхолдеров (государства, территориальных общин, бизнес-структур, инвесторов, образовательных и научных учреждений). The article is devoted to the study of the role of territorial communities in ensuring the sustainable development of innovative integrated structures of the different types during the intensification of the process of decentralization of power and governance in Ukraine. The essence of integration cluster formations was characterized and the expediency of using the modern technologies of the strategic management for the effective management of the creation and functioning of the innovative integrated structures within the territories was stated. The key criteria of the evaluation of the results of decentralization’s implementation are: redistribution of powers, financial base of the local self-government authorities, transparency, accountability and public participation, sustainable development and competitiveness of the territories, quality and accessibility of public services, management and coordination of the reform presented. The analysis of regional differences about the quantity of the United territorial communities and level of coverage by them the population, indicators of the financial support of the decentralization have shown that there are contradictory tendencies in the development of territorial communities and volumes of their funding, which suggests the appropriateness of further reform of decentralization on the basis the improvement of existing methods, levers and tools for its implementation. The positive effect from the development of innovative integrated structures for the main stakeholders (state, territorial communities, business structures, investors, educational and scientific institutions) has been determined. For the territorial communities, such effect is the complex consideration of the territorial specificity of the economic and social development, increasing the revenues to the local budgets, optimization of using of the territorial potential of the territory, development the innovative infrastructure of the regions, solving the urgent socio-economic and environmental problems of the territory, introduction a smart approach in the organizational and management activity. It was stated that under current conditions, clustering tools are an effective means of ensuring sustainable development of the territories, more rational using of available resources of the community, creation of the favourable business environment, improving the level and quality of life of the population of the community.
Роль территориальных общин в обеспечении развития инновационно-интегрированных структур в условиях децентрализации
The Role of Territorial Communities in Ensuring the Development of Innovative Integrated Structures in Conditions of Decentralization
Keywords: територіальна громада; інноваційно-інтегрована структура; децентралізація; органи місцевого самоврядування; регіональний розвиток; территориальная община; инновационно-интегрированная структура; органы местного самоуправления; региональное развитие; децентрализация; territorial community; innovative integrated structure; decentralization; local self-government authorities; regional development